Abates não inspecionados de ovinos em propriedades rurais no município de Tauá (CE): uma análise das características do ambiente institucional - Souza, Juan Diego Ferelli de (2013)
The non-inspected slaughter is a serious problem that affects the sheep-raising sector in Brazil. Estimates indicate that more than 90% of the sheep meat traded nationwide, is carried out in non-inspected places. Several are the agents of this production chain who perform the non-inspected slaughter, among whom are farmers. The aim of this study was to analyze, from the perspective of institutional environment, the reasons that lead farmers to carry out slaughter on farm, as a commercial activity, at the city of Tauá (CE), Brazil. Under this scope, comparative analyzes of the socioeconomic, technological and marketing of farmers who do not slaughter their sheep were performed, as well as with sheep-slaughterer farmers in the county. The city of Tauá was chosen as the location for this study due to its importance to sheep sector in Ceará State and the Northeastern Brazil. Using the survey research methodology, 336 sheep-raising farmers were interviewed. The following methods were used for statistical analysis: chi-squared test, Mean-testing and Fisher's exact test. The results demonstrated that 16.7% of the producers perform sheep slaughtering, while 83.3% usually trade live sheep to dealers. The theoretical referencing used was the New Institutional Economics and literature on the informal economy, from which hypotheses were developed, about possible determinants for farmers decision.. Eight determinant factors were identified and 2 distinguishing characteristics of producers who slaughter, from those who do not, in the Tauá county.